2012
DOI: 10.1007/s00404-012-2589-7
|View full text |Cite
|
Sign up to set email alerts
|

MRP2 (ABCC2, cMOAT) expression in nuclear envelope of primary fallopian tube cancer cells is a new unfavorable prognostic factor

Abstract: ObjectiveTo determine the prognostic value of the immunohistochemical evaluation of the multidrug resistance-associated protein 2 (MRP2) expression, together with its subcellular localization in primary fallopian tube carcinomas (PFTCs).MethodsThe immunohistochemical analysis was performed using samples originating from 70 patients with PFTCs.Results(1) We documented that MRP2 can be localized in the plasma membrane (MRP2c), as well as in the nuclear envelope (MRP2n) of the PFTC cells. (2) Patients with more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…between MRP2 up-regulation and resistance towards platinum-based chemotherapy in ovarian cancer (Materna et al, 2005), small cell lung cancer (SCLC) (Halon et al, 2007). In a transport study with membrane vesicles, (Cui et al, 1999) it was found that MRP2-transfected HEK-293 cells showed higher V max and K m for anticancer agents.…”
Section: Symbolmentioning
confidence: 98%
“…between MRP2 up-regulation and resistance towards platinum-based chemotherapy in ovarian cancer (Materna et al, 2005), small cell lung cancer (SCLC) (Halon et al, 2007). In a transport study with membrane vesicles, (Cui et al, 1999) it was found that MRP2-transfected HEK-293 cells showed higher V max and K m for anticancer agents.…”
Section: Symbolmentioning
confidence: 98%
“…Abnormal expression of MRP1 increases the efflux of Doxorubicin reducing its cytotoxic potential in ovarian cancer, leukemia and non-small cell lung cancer cells [160][161][162] . NRF2 dependant MRP2 upregulation has been reported to be a cause of resistance towards platinum based therapy in small cell lung cancer and ovarian cancer [163,164] ; Tamoxifen therapy towards breast cancer cells [165] . MRP3 was found to be more highly expressed in NSCLC than in SCLC, and NRF2 dependent MRP3 over expression causes intrinsic resistance of NSCLCs to anticancer drugs like vincristine, etoposide and Cisplatin [162] .…”
Section: Phase II Drug Metabolizing Enzymesmentioning
confidence: 99%
“…This was similar to most studies in the literature. 29,30 Although comprehensive staging of PFTC included pelvic and para-aortic lymphadenectomy in the National Comprehensive Cancer Network guidelines, 5 its role in the survival of PFTC remained controversial in the literature. For patients with positive lymph node involvement, the means of OS and DFS have been reported to be significantly shorter than those of the patients with negative lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%